ANALISIS PEMASARAN PRODUK SUSU ENTRASOL PADA PT. KALBE NUTRITIONALS PEKANBARU - lili erti (Jurnal Ilmiah Ekonomi Dan Bisnis, 2017)
Abstract: The product something that can be offered to meet the needs or desire .The productis everything that can be offered by producers asked, sought, bought, used, or consumed bythe market. Products offered include physical goods, services, place, and ideas. The purposeof this study to analyze the marketing strategies used in marketing milk Entrasol At PT. KalbeNutritional Pekanbaru. This study uses accidental sampling with a sample size of 120 people.Methods of data analysis using descriptive method by collecting, classifying and tabulatingdata. The result is the factors that led to increased realization of the target marketing of dairyproducts Entrasol at. Kalbe Nutritionals Pekanbaru (1) a factor in terms of product quality,packaging, sizes and kinds are good (2) factors that led to increased price realizationpenteapan marketing terms, the price of competitors and compliance with quality price isappropriate. (3) promotion factor in terms of advertising, personal selling and sales promotionare excellent. (4) and the factors of competitors in terms of the threat of new entrants andcompetition brand, product Entrasol expressed interest. This is leading to an increasingrealization of the target marketing of dairy products Entrasol at. Kalbe Nutritionals Pekanbaruin years 2014-2015.Keywords:Marketing, Product, Promotion, Price, Competition